INTERNET ENABLED PUBLIC SERVICES AS A DRIVER OF ECONOMIC GROWTH -CASE STUDY ECROATIA 2006 - - Novotny, Damir; Sabati, Zvonimir (Journal of Information and Organizational Sciences, 2007)
The Barcelona European Council called on the European Commission to draw up an eEurope Action Plan in order to widespread penetration of ICT, as powerful driver of growth and employment. Availability of modern on-line public services through e-Government, e-Learning, e-Health and e-Business is to be secured by the Action Plan. The eEurope 2005 is succeeding eEurope 2002 Action Plan which comprises four separate but interlinked tools: policy measures, exchange of good practices, monitoring and benchmarking and overall co ordination of existing policies. Croatia is candidate for accession to EU by 2009, which means that Croatian Government has to implement eEurope Action plan 2005 and Commission’s new strategic framework, i2010 - European Information Society 2010. In first part of the paper authors are presenting overall framework of eEurope Action Plan 2005 as well i2010 strategic framework. For the purposes of the paper, authors have conducted a research availability of on-line public services through government, e-Learning, e-Health and e-Business in Croatia 2006.The results of the survey has been benchmarked to the results of similar surveys in New Europe countries.